2021
DOI: 10.1332/239868020x15850132209691
|View full text |Cite
|
Sign up to set email alerts
|

Gender-based violence: a five-country, cross-sectional survey of health and social care students’ experience, knowledge and confidence in dealing with the issue

Abstract: Health and social care professionals are well placed to identify and respond to those affected by gender-based violence; yet students across a range of health disciplines describe a lack of knowledge, preparation and confidence in dealing with the issue. Our study aimed to explore health and social care students’ perceptions of their own knowledge and confidence on the subject of gender-based violence, recollections of gender-based violence learning opportunities through university and clinical placements, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 25 publications
1
5
0
1
Order By: Relevance
“…Students and academic staff across all three countries indicated that GBV had been insufficiently or incompletely addressed within their curricula. This finding mirrors conclusions from our previous research (Bradbury-Jones et al, 2021) and other international studies (Bradbury-Jones & Broadhurst, 2015;Doran & Hutchinson, 2017;Valpied et al, 2017). All participants agreed that GBV ought to have a place on their curricula, although some suggested that the subject has greater importance for certain professional groups.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Students and academic staff across all three countries indicated that GBV had been insufficiently or incompletely addressed within their curricula. This finding mirrors conclusions from our previous research (Bradbury-Jones et al, 2021) and other international studies (Bradbury-Jones & Broadhurst, 2015;Doran & Hutchinson, 2017;Valpied et al, 2017). All participants agreed that GBV ought to have a place on their curricula, although some suggested that the subject has greater importance for certain professional groups.…”
Section: Discussionsupporting
confidence: 87%
“…This article reports on the final part of a larger funded study, consisting of three prior phases: (1) a systematic review of effective educational strategies in GBV (Sammut et al, 2021); (2) a cross-sectional survey exploring HSC students' knowledge and confidence in addressing GBV (Bradbury-Jones et al, 2021); and (3) development of a GBV e-learning resource (available at: https:// www. notti ngham.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…While this is a valid viewpoint, it does imply that perhaps there is room for more teaching on a wide variety of safeguarding issues, one of them being FGM. This is supported by an international cross-sectional study on gender-based violence education 13 which found that health care students were underprepared and lacked con dence in dealing with these issues in practice. It concluded that there is a need for healthcare education programmes to include more clinical teaching on these topic areas.…”
Section: Discussionmentioning
confidence: 92%
“…In this regard, a survey of 377 students in the field of health and social assistance from five countries highlighted that most participants had not received guidance on an adequate approach to gender-based violence in university education, therefore, they did not feel prepared to intervene in situations. They also valued practical-based learning when compared to strictly theoretical discussions ( 33 ) .…”
Section: Discussionmentioning
confidence: 99%